2010
DOI: 10.1021/ol9029269
|View full text |Cite
|
Sign up to set email alerts
|

Burkholdines 1097 and 1229, Potent Antifungal Peptides from Burkholderia ambifaria 2.2N

Abstract: Potent antifungal cyclic lipopeptides, burkholdines (Bk), were isolated from a culture of Burkholderia ambifaria 2.2N. Bk-1229 (1) and Bk-1097 (2) are octapeptides comprised of nonproteinogenic amino acids, including -hydroxytyrosine, -hydroxyasparagine, and a new fatty acyl amino acid. 1 and 2 are fungicidal against a panel of fungi with potencies 2-60-fold better than amphotericin B control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 10 publications
0
43
1
Order By: Relevance
“…Many Burkholderia species exhibit a high potential for secondary metabolite production (Kang et al 1998; Partida-Martinez and Hertweck 2005; Partida-Martinez et al 2007; Knappe et al 2008; Schmidt et al 2009; Rohm et al 2010; Seyedsayamdost et al 2010; Tawfik et al 2010; Mahenthiralingam et al 2011; Franke et al 2012). As B. terrae BS001 possesses an exceptionally large genome, one might predict the ample presence of novel biosynthesis gene clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Many Burkholderia species exhibit a high potential for secondary metabolite production (Kang et al 1998; Partida-Martinez and Hertweck 2005; Partida-Martinez et al 2007; Knappe et al 2008; Schmidt et al 2009; Rohm et al 2010; Seyedsayamdost et al 2010; Tawfik et al 2010; Mahenthiralingam et al 2011; Franke et al 2012). As B. terrae BS001 possesses an exceptionally large genome, one might predict the ample presence of novel biosynthesis gene clusters.…”
Section: Resultsmentioning
confidence: 99%
“…This polyphasic taxonomic study revealed that strain MSh1 T represents a novel Bcc species, for which the name B. paludis is proposed. Based on current literature, Burkholderia species are known to produce narrow-spectrum antimicrobial compounds such as iminopyrrolidines (produced by B. plantari ) and occidiofungin ( B. contaminans ) which only targets Gram negative Erwinia amylovora and fungi, respectively (Lu et al, 2009; Tawfik et al, 2010). In this study, strain MSh1 T exhibit a different spectrum of antimicrobial activity, which targets Gram positive bacteria only, particularly strains of S. aureus and E. faecalis .…”
Section: Introductionmentioning
confidence: 99%
“…The genus Stenotrophomonas, part of the Gammaproteobacteria, is a member of the same family (Xanthomonadales) as Lysobacter, which is well known for antibiotic production (Xie et al 2012). The Betaproteobacteria isolated (Delftia, Acidovorax, Variovorax, and Achromobacter) are all Burkholderiales, which have recently showcased their biosynthetic potential with the discovery of several new bioactive compounds from Burkholderia, including the burkholdines and burkholdacs, as well as the recent discovery by our laboratory of a PK-NRP hybrid metallophore, delftibactin, produced by D. acidovorans (Biggins et al 2011;Johnston et al 2013;Lin et al 2012;Tawfik et al 2010;Xie et al 2012). Chitinophaga is the only known Bacteroidetes antibiotic producer isolated; however, Bacteroidetes have a high percentage of PKS and NRPS genes relative to their genome size, second only to the Actinobacteria, which may indicate the other isolated Bacteroidetes have unrealized biosynthetic potential and are a potential source for antimicrobial discovery (Donadio et al 2007).…”
Section: Resultsmentioning
confidence: 99%